Interest Rate Skewness and Biased Beliefs - Michael D. Bauer; Mikhail Chernov (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Conditional yield skewness is an important summary statistic of the state of the economy. It exhibits pronounced variation over the business cycle and with the stance of monetary policy, and a tight relationship with the slope of the yield curve. Most importantly, variation in yield skewness has substantial forecasting power for future bond excess returns, high-frequency interest rate changes around FOMC announcements, and consensus survey forecast errors for the ten-year Treasury yield. The COVID pandemic did not disrupt these relations: historically high skewness correctly anticipated the run-up in long-term Treasury yields starting in late 2020. The connection between skewness, survey forecast errors, excess returns, and departures of yields from normality is consistent with a theoretical framework where one of the agents has biased beliefs.
Keywords: E43; E44; E52; G12; 330; bond markets; yield curve; skewness; biased beliefs; monetary policy